Basic Income in Australia and New Zealand Perspectives from the Neoliberal Frontier - Mays, J.; Marston, G.; Tomlinson, J. (Exploring the Basic Income Guarantee, 2016)
Basic income is an innovative, powerful egalitarian response to widening global inequalities and poverty experiences in society, one that runs counter to the neoliberal transformations of modern welfare states, social security, and labor market programs. This book is the first collective volume of its kind to ask whether a basic income offers a viable solution to the income support systems in Australia and New Zealand. Though often neglected in discussions of basic income, both countries are advanced liberal democracies dominated by neoliberal transformations of the welfare state, and therefore have great potential to advance debates on the topic. The contributors' essays and case studies explore the historical basis on which a basic income program might stand in these two countries, the ideological nuances and complexities of implementing such a policy, and ideas for future development that might allow the program to be put into practice regionally and applied internationally.